2001
DOI: 10.1037/1528-3542.1.3.300
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and motivation II: Sex differences in picture processing.

Abstract: Adhering to the view that emotional reactivity is organized in part by underlying motivational states-defensive and appetitive-we investigated sex differences in motivational activation. Men's and women's affective reactions were measured while participants viewed pictures with varied emotional and neutral content. As expected, highly arousing contents of threat, mutilation, and erotica prompted the largest affective reactions in both men and women. Nonetheless, women showed a broad disposition to respond with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

102
548
13
22

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 854 publications
(685 citation statements)
references
References 29 publications
102
548
13
22
Order By: Relevance
“…This particular sensitivity of women to negative affects was previously found with SCR and other psychophysiological indices as well as with subjective ratings of emotions (Bradley, Codispoti, Sabatinelli, & Lang, 2001;Kring & Gordon, 1998). Interestingly, this gender influence was not dependent of HA scores, suggesting that BIS would not be involved in this particular sensitivity, as could have been expected regarding women's classically higher scores in HA and BIS-related scales (Hansenne et al, 2005;Jorm et al, 1999).…”
Section: Discussionsupporting
confidence: 51%
“…This particular sensitivity of women to negative affects was previously found with SCR and other psychophysiological indices as well as with subjective ratings of emotions (Bradley, Codispoti, Sabatinelli, & Lang, 2001;Kring & Gordon, 1998). Interestingly, this gender influence was not dependent of HA scores, suggesting that BIS would not be involved in this particular sensitivity, as could have been expected regarding women's classically higher scores in HA and BIS-related scales (Hansenne et al, 2005;Jorm et al, 1999).…”
Section: Discussionsupporting
confidence: 51%
“…No gender differences were found for SCR, but subjective ratings differed in Study II. Younger and older women rated the pictures as more negatively arousing than men This finding is in line with previous studies (Bradley et al, 2001;Denburg, Buchanan, Tranel, & Adolphs, 2003;Kunzman & Grühn, 2005).…”
Section: Results and Concluding Remarkssupporting
confidence: 82%
“…Bradley et al (2001) found no gender differences in SCR magnitude between younger adults, although they did find a tendency of increased magnitude towards erotic pictures in men. In the same study, women rated unpleasant pictures as being more arousing than did men.…”
Section: Electrodermal Activity: Skin Conductance Responsementioning
confidence: 73%
“…Such variance can be attributed to gender (Bradley et al 2001), personality traits, and psychobiological differences (Zuckerman 1979(Zuckerman , 1996, as well as to adaptation (Fenz and Epstein 1967). It has been hypothesized for some time, then, that an apparently aversive experience may not actually trigger strong negative feelings.…”
Section: Intensity-based Modelsmentioning
confidence: 99%